Modelling and Monitoring of Coastal Marine Processes - Murthy, C. R.; Sinha, P. C.; Rao, Y. R.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
Although numerous books have been written on both monitoring and modelling of coastal oceans, there is a practical need for an introductory multi-disciplinary volume to non-specialists in this field. The articles commisioned for this book, organized into four major themes, are written by experts in their disciplines while the text is intended for scientists who do not have extensive training in marine sciences and coastal zone management. As such, the articles in this monograph can be a valuable reference for practicing professionals. The first section introduces the complex physical processes with main emphasis on waste disposal in the coastal ocean. Following this, examples of instrumentation techniques that are commonly used for measuring different properties of oceans are discribed. Coastal and estuarine transport and dispersion modelling is introduced in the next section with examples from different parts of the world. The last section provides an overview of coastal disasters such as tropical cyclones, storm surges and oil spills.
Coastal Marine Environment: Theory & Measurements -- The Coastal Ocean -- to Transport Phenomena -- Coastal Marine Diffusion Processes -- Measurement of Currents in the Coastal Oceans -- Remote Sensing Applications to Coastal Oceanography -- Modelling of Coastal Marine Pollution -- Coastal Transport and Dispersion Modelling -- Modelling Circulation and Salinity in Estuaries -- Modelling and Measurement of Sediment Transport in Lakes -- Coastal Marine Hazards -- Storm Surges: Worst Coastal Marine Hazard -- Deterministic Methods for Prediction of Tropical Cyclone Tracks -- Risk Analysis for Oil Spillage in Marine Environment -- Coastal Marine Policy/Management -- National Legislations and International Conventions for Regulation of Coastal Zone Activities -- Central Considerations in Initiating and Operating Programmes in Integrated Coastal Management -- Geographic Information Systems for Integrated Coastal Resource Management -- Integrated Coastal Area Management: The Case of India.
Keywords: Earth sciences; Hydrogeology; Oceanography; Physical geography; Aquatic ecology; Water pollution; Earth Sciences; Hydrogeology; Physical Geography; Oceanography; Freshwater & Marine Ecology; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Electronic books